Functional and Radiological Outcome of Protrusio Acetabuli Managed with Total Hip Arthroplasty - R Raj Kishore; R Arokia Amalan; EMV Muthu Subash (Journal of Orthopedics and Joint Surgery)
Background: Primary migration of the femoral head into the acetabulum (Protrusio) is something not seen very often. It is seen in hip arthritis secondary to ankylosing spondylitis, rheumatoid arthritis (RA), Paget's disease and previous trauma. Primary total hip replacement (THR) can be demanding technically as there is significant proximal and medial migration of the joint center and reduced bony support to the acetabular component placed at the rim. Aim and objective: To analyze the functional and radiological outcome of Protrusio acetabuli managed with total hip arthroplasty (THA). Materials and methods: This study has been conducted in the Department of Orthopaedics, Medical College Hospital, Tirunelveli, Tamil Nadu, India, during the period of December–November 2022 and is a prospective study. The morselized femoral head, antiprotrusio cage, and multihole cup were used in this study. Clinical outcome was determined by using Harris hip score. Results: Patients were followed up every month for a period of 2 years. X-rays were taken during each follow-up to assess the graft incorporation and cup position, and patients are examined clinically by assessing a range of movements, and pain during movements. In our study, most of our patients have a moderate (5–15 mm) grade of protrusion. In our study group, we've encountered about 10% of complications including distal femur fracture and nerve injury. The preoperative (pre-op) mean Harris hip score of 48 has been increased to 78.4 in our study. Conclusion: Total hip arthroplasty (THA) overseen utilizing impacted morselized bone graft along with cementless metal modular cups with trabecular lining was powerful in managing people with various grades of protrusion. The impacted graft is used in acetabular reconstruction for restoring the medial wall, providing a buttress for the acetabular implant to be seated, and lateralizing the implant to restore the center of the hip. However, structural issues with the acetabulum should be carefully considered and potential defects include problems with the weak acetabulum and a thin acetabular wall.